Financial Performance Analysis Using EVA, MVA, REVA, FVA, and SVA Methods in Telecommunication Companies Listed in the LQ45 Index - Dani, Novita Rahma; Widuri, Trisnia (Universitas Muhammadiyah Pontianak, 2025)
This study aims to analyze the financial performance of telecommunication companies listed in the LQ45 Index for the 2022–2024 period using Economic Value Added (EVA), Market Value Added (MVA), Refined Economic Value Added (REVA), Financial Value Added (FVA), and Shareholder Value Added (SVA) methods. The research applies a descriptive quantitative approach with secondary data from annual financial statements obtained from the Indonesia Stock Exchange. The results indicate that EVA, FVA, and SVA are positive, meaning firms create economic value. Meanwhile, MVA and REVA tend to fluctuate or turn negative, indicating limitations in enhancing market value.